Ectopic Hepatic Tissue Presented as a Posterior Mediastinal Mass. (25th November 2010) - Rozen, Eugene; Stephens, Gary; Asarian, Armand; Xiao, Philip
Abstract : We present a young patient with respiratory complaints that was found to have a mass in her right posterior mediastinum. The mass was diagnosed to be ectopic histologically unremarkable hepatic tissue. We have also reviewed several of the few intrathoracic ectopic liver cases in the literature, along with a brief discussion of the significance of such a finding.